Effect of vitamin D supplementation on polycystic ovary syndrome: A systematic review and meta-analysis of randomized controlled trials. (February 2017) - Fang, Fang; Ni, Ke; Cai, Yiting; Shang, Jin; Zhang, Xiaoke; Xiong, Chengliang
Abstract: Objective: To evaluate the effect of vitamin D supplementation on patients with PCOS. Methods: We performed a literature search in database and identified all of the RCTs published before December 2015 that compared the effect of vitamin D supplementation with placebo or metformin in PCOS patients. Main results: Nine out of 463 identified studies were included, involving 502 women presenting with PCOS. Vitamin D supplementation had significant effect on the improvement of follicular development with a higher number of dominant follicles (OR, 2.34; 95% CI, 1.39 to 3.92). Differences in regular menstrual cycles were also observed when metformin plus vitamin D was compared with metformin alone (OR, 1.85; 95% CI, 1.01 to 3.39). Conclusions: Evidence from available RCTs suggests vitamin D supplementation may be beneficial for follicular development and menstrual cycle regulation in patients with PCOS. Additional high-quality RCTs are required to confirm the effectiveness of vitamin D on PCOS.